Analisis Strategi Promosi terhadap Penerimaan Siswa Baru pada SMK IPTEK Cilamaya - Fajar Adhi Purwaningrum; Ujang Sumarjono (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze promotional strategies for new student admissions at SMK IPTEK Cilamaya. Data were obtained through observation, interviews and questionnaires. This type of research is a qualitative analysis of the data available at the school. The analysis technique used is SWOT analysis, which is data processing to obtain the results of analyzing internal factors (strengths and weaknesses) and external factors (opportunities and threats). The indicators used in this study are product indicators and promotion indicators. The results of research to 81 respondents showed that in the product indicator the highest results were obtained in the strongly agree category with a score of 289 or 26.83%, while in the promotion indicator the highest results were obtained in the disagree category showing a score of 285 with a percentage of 29.05%,